2004
DOI: 10.1523/jneurosci.1596-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

In VitroIschemic Tolerance Involves Upregulation of Glutamate Transport Partly Mediated by the TACE/ADAM17-Tumor Necrosis Factor-α Pathway

Abstract: A short ischemic event [ischemic preconditioning (IPC)] can result in a subsequent resistance to severe ischemic injury (ischemic tolerance). Although tumor necrosis factor-␣ (TNF-␣) contributes to the brain damage found after cerebral ischemia, its expression and neuroprotective role in models of IPC have also been described. Regarding the role of TNF-␣ convertase (TACE/ADAM17), we have recently shown its upregulation in rat brain after IPC induced by transient middle cerebral artery occlusion and that subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 68 publications
14
86
1
Order By: Relevance
“…Of note, whereas the staining in neurons is clearly located in the membrane, this is not the case in astrocytes. In this context, using an in vitro model of IPC (Romera et al, 2004), we have recently demonstrated that IPC induces a different regulation of TACE in each cell type, with an increase in mature TACE and a decrease in its precursor, consistent with a regulation by processing, in neurons, and an increase in the expression of the precursor form, suggesting a regulation at the transcriptional level, in astrocytes. This is consistent with our new data, because the precursor form of TACE has been described to be located intracellularly, whereas the mature form is predominantly in the plasma membrane (Schlöndorff et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Of note, whereas the staining in neurons is clearly located in the membrane, this is not the case in astrocytes. In this context, using an in vitro model of IPC (Romera et al, 2004), we have recently demonstrated that IPC induces a different regulation of TACE in each cell type, with an increase in mature TACE and a decrease in its precursor, consistent with a regulation by processing, in neurons, and an increase in the expression of the precursor form, suggesting a regulation at the transcriptional level, in astrocytes. This is consistent with our new data, because the precursor form of TACE has been described to be located intracellularly, whereas the mature form is predominantly in the plasma membrane (Schlöndorff et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, it is noteworthy that although proinflammatory cytokines and mediators are clearly associated with tissue damage in autoimmune neuropathies, some of them have been linked to normal function of the nervous system and even neuroprotection in some cases (45). Particularly, TNF-␣ is produced by astrocytes, microglia, and neurons and has been associated both with CNS damage and neuroprotection against excitotoxicity following ischemia or stroke (45)(46)(47)(48)(49). In contrast, IFN-␥ is produced only by infiltrating leukocytes but not by resident cells in the CNS, thus making this cytokine a better target for immunotherapy than TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…The proper functioning of glutamate uptake is critical to prevent glutamate-induced damage to oligodendrocytes, and positive regulators of the expression of glutamate transporters have a protective potential, as they contribute to ischaemic tolerance after ischaemic preconditioning. 79 Another set of molecular targets to prevent glutamate insults to oligodendrocytes lie downstream of glutamate receptor activation (see Figure 5). For instance, tetracyclines, which attenuate mitochondrial damage subsequent to insults including excitotoxicity, protect oligodendrocytes and white matter, making these antibiotics promising candidates for the treatment of acute and chronic diseases with oligodendrocyte loss.…”
Section: Mü Ller Cells and Retinopathymentioning
confidence: 99%